Analysis of Factors Influencing Employee Performance at the Regional Civil Service Education and Training Agency of Pohuwato Regency - Ibrahim, Meimoon; Suyanto, Mohamad Afan; Karundeng, Deby Rita; Husain, Lukman Is (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2024)
This research aims to analyze the factors influencing employee performance at the Regional Education and Training Personnel Agency of Pohuwato Regency. The sample targeted for the study consists of 33 individuals, all of whom participated as respondents using multiple linear regression. Based on the analysis, it was found that the decision-making mechanism variable has a positive but non-significant effect on employee performance, the management professionalism variable has a positive and significant effect on employee performance, the supervision and control mechanism variable has a positive and significant effect on employee performance, and the decision-making mechanism, management professionalism, and supervision and control mechanisms collectively have an effect on the performance of the Regional Education and Training Personnel Agency of Pohuwato Regency employees.